(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: First-generation older migrants in high income countries are more likely to be less physically active than non-migrants. However, there is a lack of literature on barriers and enablers to participation in physical activity for community-dwelling first-generation older Black Africans in the United Kingdom (UK). The aim of this research was to explore the attitudes, preferences, experiences, and health behaviours associated with participation in physical activity among community-dwelling first-generation older Black Africans in the UK. Methods: Twelve people (6 females) aged 44–62 years from the target population were interviewed using a topic guide based on the findings of a scoping review and the Behaviour Change Wheel framework. Interviews were audio-recorded and transcribed manually before being imported into NVivo software. Thematic analysis was conducted by generating codes and mapping them against the COM-B (Capability, Opportunity, Motivation-Behaviour) model and the TDF (Theoretical Domains Framework). Results: Around two-thirds of participants self-reported not meeting the UK’s Chief Medical Officers physical activity recommendations, which were explained by the following diverse and intertwined factors: 1. Psychological capability: knowledge – all participants self-reported lacking awareness about the guidelines on physical activity; 2. Social opportunity: social norms – physical activity facilities and settings in the United Kingdom were reported as culturally inappropriate; 3. Physical opportunity: Environmental contexts and resources – lack of money to afford gym, lack of time, and safety concerns in physical activity settings in public places; and 4. Reflective motivation: goal priority – life commitments, including needing to work for money and family responsibilities, were considered more important than doing regular physical activity. On the other hand, the key enablers to physical activity among participants appeared to be reinforced (automatic motivation) by cues to action (illnesses such as diabetes) and routines (walking being imbedded in activities of daily living such as the workplace, commuting to work and shopping, and household activities). Conclusion: The findings of this research will support future work to co-produce physical activity interventions to reduce insufficient physical activity levels in the community-dwelling first-generation older Black Africans in the UK